Solve all your doubts with Teachoo Black (new monthly pack available now!)
Ex 3.3
Ex 3.3, 2 Important
Ex 3.3, 3 Important
Ex 3.3, 4
Ex 3.3, 5 (i) Important
Ex 3.3, 5 (ii)
Ex 3.3, 6 Important
Ex 3.3, 7
Ex 3.3, 8 Important
Ex 3.3, 9 Important
Ex 3.3, 10
Ex 3.3, 11 Important
Ex 3.3, 12
Ex 3.3, 13 Important You are here
Ex 3.3, 14
Ex 3.3, 15
Ex 3.3, 16 Important
Ex 3.3, 17
Ex 3.3, 18 Important
Ex 3.3, 19
Ex 3.3, 20
Ex 3.3, 21 Important
Ex 3.3, 22 Important
Ex 3.3, 23 Important
Ex 3.3, 24
Ex 3.3, 25
Ex 3.3
Last updated at Sept. 3, 2021 by Teachoo
Ex 3.3, 13 Prove that cos2 2𝑥 – cos2 6𝑥 = sin4𝑥 sin8𝑥 Solving L.H.S. cos2 2x – cos2 6x Using a2 – b2 = (a + b) (a - b) = (cos 2x + cos 6x) (cos 2x – cos 6x) Lets calculate (cos 2x + cos 6x) and (cos 2x + cos 6x) separately Hence cos2 2𝑥 – cos2 6𝑥 = (cos2𝑥 + cos6𝑥) (cos2𝑥 – 6𝑥) = (2 cos〖4𝑥 cos〖(−2𝑥)〗 〗 ) (−2 sin4𝑥 (sin〖(−2𝑥)〗 )) = (2 cos〖4𝑥 cos〖(2𝑥)〗 〗 ) (−2 sin4𝑥 (〖−sin〗〖(2𝑥)〗 )) = (2 cos〖4𝑥 cos〖(2𝑥)〗 〗 ) (2 sin4𝑥 sin〖(2𝑥)〗 ) = (2 sin4𝑥 cos4𝑥) (2 sin2𝑥 cos2𝑥) = sin8𝑥 sin4𝑥 = R.H.S. Hence, L.H.S. = R.H.S. Hence proved